Hyperon forward spin polarizabilty ү0; Physical Review D; Vol. 84, iss. 7 - Kumar K. B. V.; Faessler A.; Gutsche T.; Holstein B. R.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2011, 2011)
Title screen